Relasi Kuasa Komunitas Anti Riba di Surabaya dalam Penolakan Bunga Kredit Perbankan - Widodo, Fakhrial Erdiasyah (Paradigma, 2023)
People gather together to form a community. There is a unique community in Surabaya based on religious beliefs. This community is called the anti-usury community. This community is famous for challenging the practice of usury. Usury is considered a form of unfair financial exploitation. In rejecting bank loan interest, they hold several activities such as seminars, sharing, and mentoring. In conducting socialization, they are based on the Qur’an and hadith. This community aims to create a true Muslim society that avoids usury as much as possible. This research will be discussed using Michel Foucault’s power relations perspective. The research method is qualitative using an ethnomethodology approach. Subject selection uses purposive sampling techniques to realize focused research. Furthermore, data analysis uses the perspective of Miles & Huberman, namely data reduction, data modeling, and verification which are then drawn conclusions. The results of the data findings show that the objective conditions of community members have the same condition, namely their economic downturn. They then joined this community to solve the debt problem. Furthermore, they follow the doctrine socialized by the anti-usury community as a form of power relations.